Development of a Sesotho health literacy test in a South African context - Marianne Reid; Mariette Nel; Ega Janse van Rensburg-Bonthuyzen (AOSIS, 2019)
Background: Research shows that poor health literacy (HL) can be a threat to health and health care. Health literacy is under-researched and poorly understood in developing countries, including South Africa, because of the absence of language and context-specific HL tests. Aim: The researchers aimed to develop an appropriate HL test for use among South African public health service users with Sesotho as their first language. Setting: The test was developed in the Free State Province of South Africa, for use among Sesotho speakers. Methods: Mixed methods were employed to develop the Sesotho Health Literacy Test (SHLT). The process of developing the test was carried out in distinctive methodological steps. Results: The stepwise process set out by identifying abstracts (n = 206) referring to HL tests. Sourcing of HL tests followed a tapered process resulting in the use of 17 HL tests. Elements within a conceptual framework guided HL test item selection (n = 47). Two Delphi sessions assisted in reaching consensus regarding final HL test items (n = 40). The readability testing of the SHLT tested 4.19 on the Coleman-Liau Index score. A context-suitable and comprehensive SHLT ensued from this work. Conclusion: The SHLT assessment instrument development creates a platform for HL testing among Sesotho first language speakers in South Africa. The context-sensitive methodology is entrenched in a theoretical framework, distributing HL test items between identified competencies and related skill dimensions and domains. The methodology can be applied to the development of HL tests for other languages and population groups in developing countries.